Bimetallic dioxidovanadium(V) complex containing a malonohydrazide derivative ligand: Synthesis, characterization, and crystal structure - Kurbah, Sunshine Dominic (European Journal of Chemistry, 2022)
In this paper, we report the synthesis and characterization of the dioxidovanadium(V) complex derived from a malonohydrazide ligand (N'1,N'3-bis(2-hydroxybenzylidene) malonohydrazide). The newly synthesized complex was characterized by infrared spectroscopy (IR), nuclear magnetic resonance (NMR), and the structure of the complex was also established by a single crystal X-ray diffraction study. The bimetallic complex crystallizes in the triclinic space group P-1 with the following parameters a = 10.8273(5) Å, b = 11.4677(6) Å, c = 15.0366(8) Å, α = 81.591(4)°, β = 83.018(4)°, γ = 76.326(4)°, V = 1787.23(16) Å3, Z = 2, T = 292.5(2) K, μ(MoKα) = 0.600 mm-1, Dcalc = 1.463 g/cm3, 11730 reflections measured (6.236° ≤ 2Θ ≤ 58.062°), 7981 unique (Rint = 0.0231, Rsigma = 0.0506) which were used in all calculations. The final R1 was 0.0496 (I > 2σ(I)) and wR2 was 0.1255 (all data). The ligand was coordinated to the metal ions in a tridentate fashion through the donor O/N/O atoms. The metal ions adopted a square pyramidal geometry with slight distortion. Reaction of the complex with hydrogen peroxide was also carried out, and it was found that the complex reacts with hydrogen peroxide to form a peroxo complex.